2014
DOI: 10.1080/00207233.2014.988550
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations of toxicity in the Georges Bay catchment, Tasmania, Australia

Abstract: North-eastern Tasmania, Australia has been an area of major production for Pacific oysters (Crassostrea gigas) for over 25 years. Since the mid-1990s, increased oyster mortality has been observed. The purpose of the present study was to identify the agent causing aquatic toxicity and to investigate whether there is a chemical and/or toxicological link between river foam and monoculture timber plantation forests of exotic eucalypts (Eucalyptus nitens) present in the catchment area. Foam samples from the George … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Our categories for ‘season’ represent monsoon periods, which can drastically alter environmental conditions and thus likely impact fish condition. For example, Piontkovski and Al-Oufi [ 29 ] reported that the upper 30 m of water column increased by 1.2°C over the last five decades during the south-west monsoons in our study region. Such regional environmental changes may thus be driving variance in fish community condition [ 30 ].…”
Section: Discussionmentioning
confidence: 57%
“…Our categories for ‘season’ represent monsoon periods, which can drastically alter environmental conditions and thus likely impact fish condition. For example, Piontkovski and Al-Oufi [ 29 ] reported that the upper 30 m of water column increased by 1.2°C over the last five decades during the south-west monsoons in our study region. Such regional environmental changes may thus be driving variance in fish community condition [ 30 ].…”
Section: Discussionmentioning
confidence: 57%
“…The George River empties into Georges Bay (with an "s"), which is known for its oyster stocks (Mitchell et al, 2000) but has been degraded by a history of timber production, tin mining, and agriculture. Historical land-use practices in the catchment have supplied > 10 6 m 3 of sediment to Georges Bay since the late 19th century (Knighton, 1991) and continue to release pollutants into the bay (Bleaney et al, 2015;Crawford and White, 2005). The success of efforts to rehabilitate Georges Bay relies in part on reducing sediment delivery from the George River to Georges Bay to pre-disturbance levels (Batley et al, 2010;Crawford and White, 2005;Kragt and Newham, 2009;McKenny and Shepherd, 1999;Mount et al, 2005), but no pre-disturbance erosion data exist for the George River, nor do any geologically relevant erosion rates exist for any part of Tasmania.…”
Section: Introduction and The Importance Of The Georgementioning
confidence: 99%
“…This study focuses on the Georges Bay estuary in northeast Tasmania, which is known for its oyster stocks (Mitchell et al, 2000) but has been degraded by a history of timber production, tin mining, and agriculture. Historical land-use practices have supplied >10 6 m 3 of sediment to Georges Bay's primary tributary, the George River (no "s"), since the late 19 th century (Knighton, 1991) and continue to supply pollutants to Georges Bay (Bleaney et al, 2015;Crawford and White, 2005). The intensive historical industrial use of the land in the George River catchment and the threat of excess sediment delivery to the fragile estuarine environment in Georges Bay has driven state and local municipalities to focus restoration and conservation efforts on the bay.…”
Section: Importance Of Erosion Of George River and The Georges Bay Watershedmentioning
confidence: 99%